Monitoring of aflatoxin M1 residues in milk marketed in Malaysia / Siti Nabilah Basar - Basar, Siti Nabilah (2014)
Background: The purpose of this study is to investigate the occurrence of AFM1 in milk obtained from the market in Malaysia. A reliable, rapid and sensitive analytical method using liquid chromatography-tandem mass spectrometry (LC-MS/MS) method to determine the aflatoxin M1 in milk has been developed. Methods: Milk samples (69) were collected from supermarket around Puncak Alam city, Selangor state. Methodology includes simple extraction of sample by adding acetonitrile, mobile phase 4mM of ammonium acetate aqueous solution/ methanol (60:40, v/v), separation using Reverse Phase Symmetry C18 column and MS/MS analysis by using Multiple Reaction Monitoring (MRM) mode for quantitative analysis. The aflatoxin M1 LC MS/MS method was developed and validated according Commission Decision 2002/657/EC. Results: Among 69 samples, 3% of sample were found positive aflatoxin M1, with concentration level range of 0.036-0.045 ng/mL however, they were below maximum residue level (MRL) established by the European Community (EC). The limits of detection (LOO) and limits of quantifications (LOQ) were 0.01 ng/mL and 0.03 ng/mL respectively. The recovery values ranged from 86% to 93% when samples were fortified at three different concentrations. Conclusion: The method applied was successfully determined AFM1 in milk. The LOQs (0.03 ng/mL) of AFM1 detected was lower than the MRL for AFM1 in milk (0.05 ng/mL) set by the European Union. The method was sensitive, reliable, and suitable for residue confirmation analyses.